Rules of Engagement: Implementing Student-Centered Learning in Breast Imaging. Issue 1 (15th January 2020) - Jordan, Sheryl G; Deans, Elizabeth C; Johnson, Meredith; Lee, Sheila S; Beck Dallaghan, Gary L
Abstract: In response to changing learner needs, our institution launched a new translational curriculum wherein basic sciences and clinical skills were integrated, longitudinal patient care experiences provided, and earlier opportunities in specialty fields introduced to better inform residency program decisions. Medical students taking the breast imaging elective were enrolled in a breast imaging immersive experience designed to meet the School of Medicine's core competencies. In focusing the elective on a narrow range of specialized topics and skills, we labeled this experience the Breast Imaging Boot Camp. Outcome data from March 6, 2017, to April 26, 2019, have been analyzed for this report. The modifications made to the elective include: e-mailing a detailed orientation document to students prior to the start of the rotation; assigning students to diagnostic, procedural, and screening roles; the attendance of students at introductory radiology symposia; students' weekly attendance at institutional multidisciplinary and divisional breast radiologic–pathologic correlation conferences; student self-study assignments using faculty-vetted resources; student participation in breast biopsy simulation and small parts ultrasound laboratories; the development of a student-centric radiology educational website; and student-directed publishing of digital case files. Medical student feedback and course analytics indicated superior course evaluation scores reinforced by narrative feedback. In website domain utilization data, the breast file domain is the most viewed subspecialty domain. The Breast Imaging Boot Camp is a successful curriculum. Its novelty lies in both its integrated approach to medical student core competencies and its clinician educators' use of today's student-favored teaching tools.